2022
DOI: 10.3201/eid2810.220321
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial COVID-19 Incidence and Secondary Attack Rates among Patients of Tertiary Care Center, Zurich, Switzerland

Abstract: Of 1,118 patients with COVID-19 at a university hospital in Switzerland during October 2020-June 2021, we found 83 (7.4%) had probable or definite healthcareassociated COVID-19. After in-hospital exposure, we estimated secondary attack rate at 23.3%. Transmission was associated with longer contact times and with lower cycle threshold values among index patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Regarding the proportion of nosocomial infections, our data are similar to those of other authors who reported 7.4% nosocomial infection. 6 In the study published by Khan et al, 7 patients with nosocomial COVID-19 had a 30-day mortality rate of 18.5%. The mortality rate in our study was strikingly similar, 18.3%.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the proportion of nosocomial infections, our data are similar to those of other authors who reported 7.4% nosocomial infection. 6 In the study published by Khan et al, 7 patients with nosocomial COVID-19 had a 30-day mortality rate of 18.5%. The mortality rate in our study was strikingly similar, 18.3%.…”
Section: Discussionmentioning
confidence: 97%
“…Outbreaks of SARS-CoV-2 variants were investigated in three studies. Wolfensberger et al showed in a mostly unvaccinated population that high viral loads among index patients and prolonged contact time in shared rooms played critical roles in healthcare-associated Alpha variant transmission [44] . O'Grady et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many of our patients who contracted COVID-19 from an outbreak were exposed to the infection by a patient that they shared a room with. One study from Switzerland 11 observed that prolonged contact time in a shared hospital room is essential in patients acquiring a HA infection.…”
Section: Discussionmentioning
confidence: 99%